2022
DOI: 10.3390/agronomy12092086
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid Improves Plant Yield, Antimicrobial Activity and Essential Oil Composition of Oregano (Origanum vulgare L. subsp. hirtum (Link.) Ietswaart)

Abstract: The effects of humic acid on plant yield, essential oil content, the composition of essential oil and the antimicrobial activity of Origanum vulgare L. subsp. hirtum (Link.) (cv. Tinmaz) cultivated in 2017 and 2018 under Eskisehir ecological conditions were evaluated. Three humic acid (HA) doses in response to 50.0 L ha−1 (HA 50), 30.0 L ha−1 (HA 30) and 0.0 L ha−1 (HA 0, as control) were applied to soil at the vegetative stage and beginning of the blooming stage of the plant throughout each harvest in both ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Oregano ( O. vulgare L.) is a fragrant and perennial plant belonging to the Lamiaceae family that originates from the Mediterranean region and has numerous applications in the food and pharmaceutical industries. In addition to its wide use as a spice and condiment, oregano is known for the unique composition of its valuable essential oil, primarily found in the inflorescences, leaves, and stems of plants [ 1 ]. The aerial parts of the plant are significant sources of polyphenols, flavonoids, triterpenoids, carvacrol, and thymol, compounds known for their strong bioactivity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oregano ( O. vulgare L.) is a fragrant and perennial plant belonging to the Lamiaceae family that originates from the Mediterranean region and has numerous applications in the food and pharmaceutical industries. In addition to its wide use as a spice and condiment, oregano is known for the unique composition of its valuable essential oil, primarily found in the inflorescences, leaves, and stems of plants [ 1 ]. The aerial parts of the plant are significant sources of polyphenols, flavonoids, triterpenoids, carvacrol, and thymol, compounds known for their strong bioactivity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectra were taken at 70 eV with a mass range of m/z 35–450. The GC oven temperature was kept at 60 °C for 10 min and programmed to be 220 °C at a rate of 4 °C/min and kept constant at 220 °C for 10 min and then programmed to be 240 °C at a rate of 1 °C/min [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…Few reports on chemical composition and biological activities of the EO of O. heracleoticum are available in the literature [ 17 , 27 , 28 , 29 , 30 ]. Napoli and coworkers reported data on variation in the aromatic profile of essential oils from a 3-year cultivation trial of Origanum vulgare subsp.…”
Section: Introductionmentioning
confidence: 99%
“…A study on Origanum vulgare subsp. hirtum from Turkey rich in carvacrol and γ-terpinene showed that this EO could be used to combat increasing resistance to antibiotics and can be an alternative in the food preservation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%